Financial difficulty, worry about affording care, and benefit finding in long‐term survivors of cancer. Issue 4 (8th March 2018) - Jones, Salene M.W.; Walker, Rod; Fujii, Monica; Nekhlyudov, Larissa; Rabin, Borsika A.; Chubak, Jessica
Abstract: Objective: To examine the associations of worry about affording care and reporting financial difficulties with benefit finding in long‐term cancer survivors. Methods: Long‐term survivors of cancer ( n = 547) in 3 integrated health care delivery systems completed the Medical Expenditure Panel Survey Cancer Survivorship Supplement. The relationship between benefit finding (becoming a stronger person, coping better, and making positive changes) and the potentially interacting factors of worry about affording care and financial difficulties was examined using multivariate logistic regression models. Results: Of the total sample, 20% reported worry and 15% reported financial difficulty. Among those who reported no worry, financial difficulty was positively associated with becoming a stronger person (odds ratio [OR] = 2.89, 95% CI: 1.07, 7.80). Coping better was not associated with worry, financial difficulties, or the interaction of the two. Among those with no financial difficulty, worry was positively associated with making positive changes (OR = 2.64, 95% CI: 1.41, 4.96), and among those reporting no worry, financial difficulty had a non‐significant positive association with making positive changes (OR = 1.98, 95% CI: 0.91, 4.31). Among those reporting worry, having financial difficulties was associated with lower odds of making positive changes (OR = 0.32, 95% CI: 0.13, 0.78). Conclusions: Our results suggest a complex relationship between financial difficulty, worry, and benefit finding. The combination of worry about affording care and financial difficulty needs to be addressed and further studied among cancer survivors, as the presence of both, but not alone, was negatively associated with making positive changes, an aspect of benefit finding.